Syphills seroprevalwence in htv-negative pregnant women, using 3 diagnostic tests: VDRL, ELISA M and TPHA - Brandão , J.E.C.; Nina, M.P.S.N.; Cervelli, K.; Obrar, A.M.; Terra, A.S.; Sion, F.; Ribeiro, L.C.P.; Vasconcellos, M.; Melca , L.A.; Morais e Sá, C.A.; Asensi, M.D.; Pessoa Silva, L.G. (Brazilian Journal of Sexually Transmitted Diseases, 2002)
The syphilis is a chronic infection with several clinicai manifestations that happen along varied stages. In spite of ils decline last decade. it has bccn again. an important problem of public health. In Brazil. the prevalcnce average of 4.0% for VDRL in pregnant woman assisted in public Services. In the pregnancy constitutes important problem. for the gravity of lhe lesions and for the real possibility of the drugs prophylaxis . It is very difficulty of proceedmg to the diagnosis in this phase, and still even with appropriate trealment. during the pregnancy the fetal infection can happen in more than 14.0% of the cases. The present study objective to determine the seroprevalence of the syphilis by means of VDRL lesl confirmed by specific confirmation.